دراسة بطريقة QSPR للطاقة والسعة الحراريتين باإلضافة الى االنتروبي على األلدهيدات األروماتية باستخدام الواصفات الجزيئية وتقنية MLR - أميرة, حفري; أمنة, عيشوش; عايدة, بوعمرة (دراسة بطريقة QSPR للطاقة والسعة الحراريتين باإلضافة الى االنتروبي على األلدهيدات األروماتية باستخدام الواصفات الجزيئية وتقنية MLR, 2022)
In this work, the QSPR method was applied, where we obtained mathematical models linking thermodynamic properties to thermal energy and capacity, in addition to entropy (Eth, Cv, S) using 3 blocks of molecular descriptors calculated by DRAGON, and also descriptors calculated by Hyperchem (QSPR properties) and databases from The two sites (swissadme, molinspiration), and this study was carried out on 77 aromatic aldehydes compounds using MLR linear regression technique, and the best results were for the basic mass (Constitional) as well as the results of the descriptors calculated by Hyperchem and the two mentioned sites.يف هذا العمل مت تطبيق طريقة QSPR حيث حتصلنا على مناذج رياضية تربط بني اخلصائص الرتموديناميكية th , Cv , S )باستعمال 3 كتل للو اصفات اجلزيئية احملسوبة للطاقة و السعة احلراريتني باإلضافة إىل األنرتويب ) E بواسطة DRAGON ,و كذلك واصفات حمسوبة ب Hyperchem( خصائص QSPR )و قواعد بيانية من املو قعني )molinspiration, swissadme, )ومتت هذه الدراسة على 77 مركب لاللدهيدات االروماتية بتوظيف تقنية االحندار اخلطي MLR , وكانت افضل النتائج للكتلة االساسية )Constitional ) وكذلك نتائج الواصفات احملسوبة بHyperchem واملوقعني املذكورين
مذكرة ماستر تخصص كيمياء
Keywords: Molecular descriptors, Physicochemical properties, QSPR, MLR technique, Aromatic aldehydes.; الواصفات اجلزيئية , اخلصائص الفيزيوكيميائية , QSPR , تقنية MLR, االلدهيدات االروماتية